Tarekat Syadziliyah dalam Dimensi Kesalehan Individual dan Kesalehan Sosial serta Pengaruh Modernisasi dan Globalisasi - Rosi Islamiyati (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2022)
This study aims to unveil the veil of human existence which is influenced by the currents of modernization and globalization, and its role with God's servants (spiritual beings). The research link in modern humans is an unbalanced self condition. Because modern humans are like machines that are constantly driven by conditions or circumstances. In the study of Sufism, at least this paper tries to answer academic anxiety about the main teachings of the Syadziliyah Order and how to maintain the outer and inner dimensions of modern humans from the influence of modernization and globalization. This research model is based on qualitative with library research data collection methods. While the data processing method uses descriptive-analysis. From the results of the study, it can be concluded that the Tarekat Syadziliyah provides an alternative balance between the worldly and spiritual dimensions, as well as social and individual piety by, first, not recommending to its students to leave the world profession. Second, do not neglect in carrying out Islamic law. Third, zuhud does not mean staying away from and hostile to the world because basically zuhud is a matter of emptying oneself from other than Allah. Fourth, there is no prohibition for the salik to become a millionaire. Fifth, trying to respond to what is currently threatening people's lives, trying to bridge the spiritual drought with world affairs that plague people's lives. Sixth, Sufism is an exercise of the soul in the context of worship and placing oneself in accordance with His provisions. Seventh, as one of the goals of tarekat and Sufism experts, two ways can be obtained, namely: Mawahib or 'ain al-jud, namely the gift that God gives to the servant he wants. Furthermore, makasib or badzi al-majhud, namely ma'rifah, will be obtained when accompanied by hard work through riyadhah, mujahadah, al-dhikr, muladzamah wuhdu, fasting, sunnah prayers.